Model Emisi Karbon Monoksida pada Kendaraan Akibat Aktivitas Transportasi di Ruas Jalan Taruna Bhakti – Jalan Kamwolker Perumnas III Kota Jayapura - Seftian Tony Gumilang; Monita Yessy Beatrick Wambrauw; Petrus Bahtiar (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2024)
The study aims to analyze the amount of carbon monoxide pollutants produced from transportation activities and per unit of vehicle on Taruna Bhakti Street – Kamwolker Perumnas III Street, to model carbon monoxide and determine the factors that influence the amount of carbon monoxide pollutants. Data processing using IBM SPSS 25 application with multiple linear regression analysis method. The average amount of CO pollutants obtained testing at the location point is 25.6 ppm or 29,296.17 μg/Nm³. And the amount of CO emissions per vehicle unit for motorcycles amounted to 725.45 ppm, gasoline cars amounted to 603.90 ppm, and diesel cars amounted to 708.57 ppm. The model obtained for testing location point 1, Y = 53,294 + 0,008 X₁ - 13,482 X₂ - 0,432 X₃ - 0,141 X₄ for location point 2 Y = 17,025 + 00,007 X₁ - 7,264 X₂ - 0,087 X₃ - 0,078X₄. And per unit of vehicles for motorcycles Y = 893,474 + 13,421X₁ - 0,447X₂ -76,970X₃, for gasoline cars Y = 603,320 + 14,862X₁ + 0,146X₂ - 97,282X₃ and for diesel cars Y = 385,146 + 23,483X₁ + 0,131X₂ - 73,392X₃. Factors that affect testing at the location point are the number of vehicles (X₁) and wind speed (X₂). For motorcycle vehicles, the vehicle maintenance factor (X₃), gasoline cars are the age of the vehicle factor (X₁), and diesel cars are the vehicle age factor (X₁).